PROMOTION OF CITIZENSHIP THROUGH MIGRATION: TAKING INTO COGNIZANCE THE PECULIARITIES OF MIGRANT - Nnawulezi, Uche; Nwaechefu, Hilary (Indonesia Law Review, 2023)
This study arose out of the growing interest in citizenship issues that have remained an intractable problem in the global migration community. The main objective this study is to examine the realities of global migration which has necessitated expansion on citizenship policies of admission, acquisition of rights, responsibilities, and interest of migrants or residents contained in statutory provisions or frameworks of migrant's country of residence. This is against the backdrop driven by the desire to create stability in the international migration system. It becomes imperative to examined the benefits and protections accorded to migrant in his place of residence which has raised issues not only touching on immigrant's economic and social facilities, but on the burden of migration on citizenship issues of migrant's place of residence. It is therefore important to reiterate the fact that there is need to create a path where migrant may move from a temporary foreign resident to a permanent citizen. It is therefore advanced that measures adopted to address the bar against citizenship for migrants around the globe should take cognizance of their peculiarities. The study adopted analytical qualitative approach and builds it's argument on existing literatures which is achieved by synthesising ideas. It argued that State that have adopted the liberal approach to democratic ideals of the rule of law must guarantee and ensure that the basic principles of human rights are provided in their municipal laws as well as in global legal frameworks. Therefore, it is necessary to consider and examined how different migration policies have been used to promote citizenship and successful incorporation of migrants within their host countries.